2010
DOI: 10.2176/nmc.50.554
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological Improvement in Patients With Cervical Spondylotic Myelopathy After Posterior Decompression Surgery

Abstract: Patients with cervical spondylotic myelopathy sometimes complain of cognitive dysfunction, which may be coincidence. However, cognitive dysfunction may be related to disorders of the cervical spine and/or spinal cord. This study investigated cognitive dysfunction in patients with cervical spinal disorders. A total of 79 patients with cervical spondylotic myelopathy (40 women and 39 men, mean age 61.2 years) underwent cervical laminoplasty between January 2006 and July 2007. Ten of these 79 patients (7 women an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 35 publications
(34 reference statements)
0
11
0
1
Order By: Relevance
“…However, emerging evidence suggest that cortical alterations may also be crucial in CSM pathology (4)(5)(6)(7). It has been shown that the cortical alterations can only partly restore after decompression surgery (8,9), and the preoperative neural activities can be used as a potential biomarker to predict surgical outcomes (10). To investigate functional alteration at the brain level in CSM patients, functional magnetic resonance imaging (fMRI), which is a highly effective method for investigating neurological and psychological conditions, has been widely applied (11)(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, emerging evidence suggest that cortical alterations may also be crucial in CSM pathology (4)(5)(6)(7). It has been shown that the cortical alterations can only partly restore after decompression surgery (8,9), and the preoperative neural activities can be used as a potential biomarker to predict surgical outcomes (10). To investigate functional alteration at the brain level in CSM patients, functional magnetic resonance imaging (fMRI), which is a highly effective method for investigating neurological and psychological conditions, has been widely applied (11)(12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…Further, recent studies have intermittently identified symptoms beyond the cord, including depression, anxiety, blurred vision, and cognitive deficits (9,(28)(29)(30)(31). However, the mechanisms underlying CSM pathophysiology at cortical level are poorly studied, and the cognitive aspects are rarely studied in CSM patients.…”
Section: Introductionmentioning
confidence: 99%
“…They hypothesize that cervical decompression can lead to improvement in symptoms by reducing cord edema, improving venous drainage, and improving cord perfusion [ 40 ]. Hoshimaru has hypothesized that improvements in neuropsychological function among patients with cervical spondylotic myelopathy after decompression surgery could be related to improvement in cerebrospinal flow within the spinal canal, which in turn would be expected to lead to improvement in cerebral blood flow [ 41 ]. These mechanisms would also be potential contributors to changes in ME/CFS and autonomic symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Another study included 79 patients with cervical myelopathy who underwent cervical laminoplasty for decompression of the cervical cord and/or cervical nerves 9. Ten of these patients with memory impairment underwent neuropsychological and neuroimaging testing.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown a decrease in cognitive performance after cervical spine injury including deficits in problem-solving ability and attention particularly in spinal cord injury 47. Interestingly, neuropsychological deficits as a result of spinal cord compression may improve after posterior cervical decompression 8 9. We present a unique case of a 34-year-old previously non-verbal male with severe signs of myelopathy and cervical stenosis that had significant neuropsychological improvement and new ability to speak and verbally communicate after anterior cervical decompression surgery.…”
Section: Introductionmentioning
confidence: 99%